Application of Integrated Curriculum in The Formation of Social Piety - Fitroh Hayati; Laksmi Dewi (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
The purpose of Islamic Religious Education (PAI – Pendidikan Agama Islam) is to form students who have noble character, who are not only righteous in worship practices, and who are not only pious individually but also socially. A curriculum that aims at achieving this goal is an integrated curriculum. This qualitative study aimed at identifying the implementation of an integrated PAI curriculum in three schools with Islamic characteristics. Data were collected through observation, documentation studies, and in-depth interviews. Interviews were conducted with principals, vice principals, PAI teachers, and students. The results showed that students' understanding of moral values in PAI learning increased through curricular activities. Meanwhile, increasing student piety was achieved through co-curricular activities.